OPTIMASI TOTAL INVENTORY COST PADA PERSEDIAAN SPARE PART ALAT BERAT DENGAN MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY - Faisal Manta (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2020)
a Heavy Equipment Trading Company, mainly dealing as the main distributor of Volvo Penta in Kalimantan, needs some revampment of their inventory planning and controlling. This company still does not have any efficient and economically structured supply chain, resulting in demands exceeding their available supply. According to purchase log in Inventory Department from September 2017 to August 2018, there had been some efforts by supply management to fix this problem by applying Economic Order Quantity (EQQ) method. The result is quite something. From 32 spare parts dealings from September 2017 to August 2018, the total spending is cut off for about 91.3 % or about Rp355.313.851,65. From that research, it could be inferred that EQQ Method is far more efficient because it can keep the purchase lower than supply method previously used.